2020
DOI: 10.1097/adm.0000000000000647
|View full text |Cite
|
Sign up to set email alerts
|

Recovery From Opioid Use Disorder (OUD) After Monthly Long-acting Buprenorphine Treatment: 12-Month Longitudinal Outcomes From RECOVER, an Observational Study

Abstract: Objectives: While evidence has mounted regarding the short-term effectiveness of pharmacotherapy for opioid use disorder (OUD), little is known about longer-term psychosocial, economic, and health outcomes. We report herein 12-month outcomes for an observational study enrolling participants who had previously taken part in a long-acting buprenorphine subcutaneous injection (BUP-XR) trial for moderate to severe OUD. Methods: The RECOVER (Remission from Chronic Opioid Use: St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 12 publications
2
40
0
Order By: Relevance
“…Despite persistent outreach efforts to contact potential study participants, only 47% of eligible participants from the parent study participated in this study. While most of the characteristics of participants in our sample were well representative of similar research ( Larochelle et al, 2018 ; Ling et al, 2020 ) (i.e. majority male, majority White, majority high school graduate), other participant characteristics are not entirely representative of the population of persons with OUD as a whole.…”
Section: Discussionmentioning
confidence: 97%
“…Despite persistent outreach efforts to contact potential study participants, only 47% of eligible participants from the parent study participated in this study. While most of the characteristics of participants in our sample were well representative of similar research ( Larochelle et al, 2018 ; Ling et al, 2020 ) (i.e. majority male, majority White, majority high school graduate), other participant characteristics are not entirely representative of the population of persons with OUD as a whole.…”
Section: Discussionmentioning
confidence: 97%
“…The use in this analysis of a composite self-report and/or UDS measure of abstinence/substance use is consistent with other RWE and observational studies of patients with OUD. Studies by Ling et al 36 and Soeffing et al 37 used self-report/ UDS data; studies by Zhu 38 and Darke 39 used self-reported abstinence data only, and a study by Leonardi et al 40 used UDS data only. Unlike a clinical trial where UDS and/or selfreport are collected for evaluating effectiveness, decisions to collect UDS in real-world clinical practice settings are determined by the care model of a particular addiction facility, by clinicians based on the specific needs and status of individual patients, or by attempts to minimize unnecessary testing.…”
Section: Discussionmentioning
confidence: 99%
“…As in the previous analysis, a 10% increase in buprenorphine adherence was observed in this new analysis, from 74% to 82%. This finding is significant because it suggests that even in this population with relatively high use of buprenorphine, using the PDT's neurobehavioral treatment led to increased medication use, a key goal of treatment [8].…”
Section: Evidence Of Long-term Real-world Reduction In Healthcare Resource Utilization Following Treatment Of Opioid Use Disorder With Rementioning
confidence: 98%